Pilgrimages and Local Islam on Java - Huub de Jonge (Studia Islamika, 1998)
For muslims with sufficient means at their disposal, the hajj the pilgrimage to Mecca, is one of the ritual obligations of their faith. It is, however, not the only pilgrimage that is made by Muslims. In almost all Islamic countries one finds sacred places that are visited by pilgrims. Indonesia, for example, has thousands of Islamic pilgrim sites scattered over the many islands. Most of them are only of local or regional importance, but some are national or even internationally renoened religious centres. The largest pilgrim sites attract hundreds of thousands of visitors each year. For a great number of sanctuaries, it is not posibble to establish when the site become a pilgromage site. Some date from pre-Islamic times and at a later date were incorporated into the Islamic tradition.DOI: 10.15408/sdi.v5i2.751